Effects of soaking soybeans in dilute acids on biologically active components - Che Man, Y.B.; Wei, L.S.; Nelson, A.I.; Yamashita, N. (Wiley, 1991)
Soaking soybeans in dilute acids affected activities of lipoxygenase, trypsin inhibitor and urease. Effects of soaking time, acid concentration and soaking temperature were investigated. Lipoxygenase activity was completely eliminated by soaking in 0.3 M HC1 at either 23°C or 40°C for 8 hr. Less than 50% trypsin inhibitor remained and urease was inactivated to an acceptable level (0.04 ΔpH).